1980
DOI: 10.1073/pnas.77.4.2224
|View full text |Cite
|
Sign up to set email alerts
|

Protease-activated “prodrugs” for cancer chemotherapy

Abstract: Many types of malignant cells and human tumors display increased concentrations of the protease plasminogen activator that converts plasminogen to the highly active protease, plasmin. Because plasmin rapidly cleaves various low molecular weight compounds coupled to appropriate peptide specifiers, we hypothesized that coupling of such peptide specifiers to anticancer drugs might create "prodrugs" which would be locally activated by tumor-associated plasmin and consequently would be less toxic to normal cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…cancer drugs might create 'prodrugs' which would be locally activated by tumor-associated plasmin and consequently would be less toxic to normal cells. For example, Carl et al [15] reported that the peptide prodrugs of several anticancer agents designed to be specific plasmin substrates showed selective cytotoxicity. Since L-valyl-ara-C is a peptidomimetic prodrug and appears to be stable in plasma or leukemia cell homogenates, the potential bioconversion of L-valyl-ara-C to ara-C in the surroundings of the leukemia cells was examined using pure plasmin.…”
Section: Discussionmentioning
confidence: 99%
“…cancer drugs might create 'prodrugs' which would be locally activated by tumor-associated plasmin and consequently would be less toxic to normal cells. For example, Carl et al [15] reported that the peptide prodrugs of several anticancer agents designed to be specific plasmin substrates showed selective cytotoxicity. Since L-valyl-ara-C is a peptidomimetic prodrug and appears to be stable in plasma or leukemia cell homogenates, the potential bioconversion of L-valyl-ara-C to ara-C in the surroundings of the leukemia cells was examined using pure plasmin.…”
Section: Discussionmentioning
confidence: 99%
“…162 was especially better than VP-16 without toxicity. The esters of unsaturated fatty acids (151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161)(162)(163)(164)(165) were better in the in vivo antitumor activity than the esters of alkanoic acids (147)(148)(149)(150) with the same number of carbons. The esters with long chain unsaturated fatty acids (C16-C22), despite lower cytotoxicity, were better in the in vivo antitumor activity than short alkanoic acid esters (138 vs. 152).…”
Section: Esters Carbonates and Carbamates Of Ddptmentioning
confidence: 99%
“…In the process of tumor metastasis, proteolytic enzymes including cathepsin B are important and a number of proteases have been reported to be expressed in metastatic carcinomas [153][154][155][156]. Several peptide-containing anticancer prodrugs targeting solid tumors have been reported [157][158][159][160][161][162][163][164][165][166].…”
Section: Enzyme Catalyzed Prodrugsmentioning
confidence: 99%
“…The pro-drug approach continues to be used in the rational design of selective anti-tumour agents (e.g. Carl et al, 1980). Human tumour xenografts such as the HT29R model system can offer an opportunity to relate the activity of these and other chemotherapeutic agents to the biochemistry of the particular tumour under investigation.…”
Section: Discussionmentioning
confidence: 99%